Overexpression of Glycerol-3-Phosphate Acyltransferase from Suaeda salsa Improves Salt Tolerance in Arabidopsis - Sui, Na; Tian, Shanshan; Wang, Wenqing; Wang, Mingjie; Fan, Hai (Frontiers in Plant Science, 2017)
Glycerol-3-phosphate acyltransferase is the first acyl esterifying enzyme in phosphatidylglycerol (PG) synthesis process. In this study, we isolated and characterized the glycerol-3-phosphate acyltransferase (GPAT) gene from Suaeda salsa (S. salsa) and obtained the full length of the GPAT gene from S. salsa (SsGPAT) by 5' and 3' RACE. The clone contained an open reading frame (ORF) of 1167 bp nucleotides that comprised of 388 amino acid residues. Real-time PCR revealed that the mRNA accumulation of GPAT in S. salsa was induced by salt stress. The highest expression levels were observed when S. salsa leaves were exposed to 300 mM NaCl treatment. At the germination stage, the germination rate and root length of overexpressed Arabidopsis strains were significantly higher than WT under different concentrations of NaCl treatments, while the inhibitory effect was significantly severe in T-DNA insertion mutant strains. In the seedling stage, chlorophyll content, the photochemical efficiency of PSII, PSI oxidoreductive activity (ΔI/Io) and the unsaturated fatty acid content of PG decreased less in overexpressed strains and more in mutant strains than that in WT under salt stress. These results suggest that the overexpression of SsGPAT in Arabidopsis enhances salt tolerance and alleviates the photoinhibition of PSII and PSI under salt stress by improving the unsaturated fatty acid content of PG.